THE EFFECT OF THE BOARDS DIRECTORS AND WOMEN AUDIT COMMITTEE ON EARNINGS MANAGEMENT - Tang, Sukiantono; Suwarsini, Lili (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2021)
Abstract: This research was conducted with the aim of examining the effect of the size of the board of directors, presence of female board of directors, female affiliate board of directors, audit committee, and female audit committee on earnings management in companies listed on the Indonesia Stock Exchange. This study uses a quantitative method by analyzing 324 companies listed on the IDX in 2015 – 2019 as a sample through purposive sampling-based sample selection. The test is done by panel data regression test with SPSS 25 and EViews 9 applications. The test was conducted using the multiple regression panel data method with a random effect model. The results of this study indicate that the size of the board of directors, female directors, female independent directors, and female affiliate directors have no significant effect on earnings management. However, the audit committee has a significant negative effect on earnings management, while female audit committee members have a significant positive effect on earnings management.Abstrak: Penelitian ini dilakukan dengan tujuan untuk menguji pengaruh ukuran direksi, keberadaan dewan direksi perempuan, dewan direksi perempuan yang terafiliasi, ukuran komite audit, dan komite audit perempuan terhadap manajemen laba pada perusahaan yang terdaftar di Bursa Efek Indonesia. Pengujian dilakukan dengan uji regresi data panel dengan program SPSS dan Eviews. Penelitian menggunakan metode kuantitatif dengan menganalisa 324 perusahaan yang terdaftar di IDX pada tahun 2015 – 2019 sebagai sampel, dimana sampel dipilih berdasarkan purposive sampling. Pengujian dilakukan dengan dengan menggunakan metode data panel regresiberganda dengan model random effect. Hasil penelitian ini menunjukkan ukuran direksi, direktur perempuan, direktur independen perempuan, dan direktur perempuan terafiliasi tidak berpengaruh signifikan terhadap manajemen laba. Sedangkan ukuran komite audit berpengaruh signifikan negatif terhadap manajemen laba, namun anggota komite audit perempuan berpengaruh signifikan positif terhadap manajemen laba.